Strategi dan Upaya Pengendalian Penyakit Tidak Menular - Safrizal, Safrizal; Fitriani, Neiliel; Nurhayati; Desiana (Bansigom Na Publisher, 2024)
Non-communicable diseases (NCDs), such as coronary heart disease, diabetes mellitus, cancer, and chronic obstructive pulmonary disease (COPD), are leading causes of global mortality and have a significant impact on public health. This article reviews effective strategies and efforts for controlling NCDs to reduce their burden and improve quality of life. The primary focus is on evidence-based approaches including public health interventions, lifestyle modifications, and health policy initiatives. The article discusses various control strategies such as promoting healthy eating, increasing physical activity, reducing alcohol consumption, and preventing smoking. Additionally, it explores the role of routine health screenings and early detection in preventing the progression of NCDs and emphasizes the importance of health education in raising public awareness. Through a review of literature and analysis of data from case studies and research reports, the article identifies successful efforts in reducing the prevalence of NCDs and improving health outcomes. Policy recommendations and implementation strategies based on these findings are expected to provide practical guidance for policymakers, health professionals, and the public in controlling NCDs.